Evaluation and Comparison of Self-Made and Commercial Calibration Markers for Radiographic Magnification Correction in Veterinary Digital Radiography - Klever, Julius; de Motte, Anastasia; Meyer-Lindenberg, Andrea; Brühschwein, Andreas (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective Magnification error is always present in radiography and calibration is necessary, if high accuracy is required in pre-surgical planning. The goal of this study was to verify the use of self-made markers and calibration techniques and to establish guidelines for magnification correction.Study Design We evaluated and compared spherical and linear markers of different sizes with focus on practicability, accuracy and precision. Markers were placed on foam pads or attached to flexible arms.Results Vertical marker deviation of 1 cm from the anatomical reference point corresponded to ∼1% of magnification error in our setting. Marker placement along the horizontal plane showed no significant magnification in the periphery of the radiograph. All markers showed good accuracy and the commercial spherical marker with a flexible segment arm had the best results regarding practicability.Conclusion Our study suggests that marker type is not solely responsible for usability and accuracy but also the type of fixation. In the absence of a calibration marker, calculation of the magnification factor using a measurement tape during radiography is equally reliable. Use of a fixed averaged calculated calibration factor showed poor agreement compared with the marker calibration, probably due to variability in size of the animals. In conclusion, if precision matters, use of a calibration marker, which could be purchased or self-made, is advised.
Keywords: calibration marker; magnification; radiography; orthopaedic surgery; implants